GEC-ESTRO/ACROP recommendations for quality assurance of ultrasound imaging in brachytherapy. (July 2020) - Siebert, Frank-André; Kirisits, Christian; Hellebust, Taran Paulsen; Baltas, Dimos; Verhaegen, Frank; Camps, Saskia; Pieters, Bradley; Kovács, György; Thomadsen, Bruce
Highlights: Ultrasound (US) quality assurance (QA) is very important to achieving consistent, high quality, image-guided implants. Ultrasound unit QA consists mostly periodic QA for the US imaging system and for the needle alignment devices. Evaluation of the US imaging capabilities requires a phantom with tests objects that show the limits of the quantity tested. Much of the alignment testing can be performed in a water tank. Abstract: Ultrasound (US) is an important imaging modality in brachytherapy (BT). In particular for low-dose-rate (LDR) and high-dose-rate (HDR) prostate implants transrectal ultrasound (TRUS) is widespread. Besides the common use of US for prostate implants, US can also be applied in gynecological and anal cancer therapies as examples amongst others. The BRAPHYQS (BRAchytherapy PHYsics Quality assurance System) and UroGEC (urology) working groups of GEC-ESTRO (GEC: Groupe Européen de Curiethérapie, committee of ESTRO: European SocieTy for Radiotherapy & Oncology) elaborated upon guidelines describing quality assurance (QA) methods for US in BT. The total quality management (QM) for the unit includes acceptance testing, commissioning and periodic image testing. In 2008, the AAPM (American Association of Physicists in Medicine) published the TG (Task group) 128 report. Whereas the TG 128 focuses on US systems and prostate BT, the current recommendations also cover tests for stepping devices and include other interstitial or intracavitary treatment sites in BT, such as anal implants and gynecological BT. The recommendations presented herein do not replace regular maintenance for the US devices performed by the vendor. They are the QA of US in BT but are not sufficient for the whole maintenance of medical US devices. Moreover, national regulations and recommendations should also be followed. For the tests presented in this report tolerances or action limits are given. These recommendations explain practical test procedures of US devices in BT. They will help the clinics to perform a high level of quality in the use of US for BT in Europe.